Problem Solving Skill Training to Reduce Disruptive Behavior and Problems with Peers in Adolescent with Oppositional Defiant Disorder - Galuh Mawarani; Primatia Yogi Wulandari (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2024)
Adolescence is a critical stage in the development of psychological issues. One common psychological condition among children and adolescents is oppositional defiant disorder (ODD). Oppositional defiant disorder (ODD) is characterized by a persistent pattern of anger or easily deviated mood, argumentative or defiant behavior, and a tendency to disrupt others around them, including adults and other authorities. This study aims to determine the effectiveness of problem-solving skills training (PSST) interventions for treating adolescents with Oppositional Defiant Disorder (ODD). The participant in this study is a 16-year-old male adolescent who was at the high school level. This study is a single-case experimental design research where participants in this experiment research provided their control data to compare within-subject designs. Instruments used in this study include observations, interviews, graphic tests, the IST intelligence test, the Child Behavior Checklist (CBCL), and the Strengths and Difficulties Questionnaire (SDQ). The results indicated that PSST intervention successfully reduced symptoms of oppositional defiant disorder (ODD), as indicated by decreases in disruptive behavior and peer-related issues, alongside improvements in problem-solving skills, contributing to enhanced adaptive functioning in interpersonal contexts, positive relationships with the environment, and psychological well-being. Consequently, an individual is better positioned for academic and social success, equipped with heightened adaptability to his surroundings.Masa remaja menjadi tahapan kritis perkembangan gejala permasalahan psikologis. Salah satu kondisi psikologis yang umum terjadi pada anak dan remaja adalah oppositional defiant disorder (ODD). ODD adalah sebuah pola kebiasaan yang berulang atau terus menerus terkait suasana hati yang marah atau mudah tersinggung, perilaku argumentatif atau menantang, atau dendam yang cenderung mengganggu orang di sekitar mereka termasuk orang dewasa maupun otoritas lainnya. Penelitian ini bertujuan untuk mengetahui efektivitas intervensi problem solving skill training (PSST) untuk menangani remaja dengan kondisi ODD. Partisipan dalam penelitian ini adalah seorang remaja laki-laki berusia 16 tahun yang berada pada tingkat sekolah menengah atas. Penelitian ini adalah penelitian single case experimental design, yaitu partisipan dalam penelitian eksperimen ini memberikan data kontrolnya sendiri dengan tujuan membandingkan desain dalam subjek. Instrumen yang digunakan pada penelitian ini adalah observasi, wawancara, tes grafis, tes kecerdasan IST, Child Behavior Checklist (CBCL), serta alat ukur Strenghts and Difficulties Questionnaire (SDQ). Hasil penelitian menunjukkan bahwa intervensi problem solving skill training (PSST) berhasil menurunkan gejala ODD yang ditunjukkan oleh penurunan perilaku mengganggu dan perilaku bermasalah dengan teman sebaya seiring dengan peningkatan keterampilan penyelesaian masalah yang berperan untuk meningkatkan fungsi adaptif dalam konteks interpersonal, hubungan positif dengan lingkungan serta kesejahteraan psikologis. Konsekuensinya, individu mempunyai posisi yang lebih baik dalam mencapai keberhasilan akademis dan sosial, serta kemampuan beradaptasi yang lebih baik terhadap lingkungannya.